Galangal, the multipotent super spices: A comprehensive review. (July 2020) - Das, Gitishree; Patra, Jayanta Kumar; Gonçalves, Sandra; Romano, Anabela; Gutiérrez-Grijalva, Erick P.; Heredia, J. Basilio; Talukdar, Anupam Das; Shome, Soumitra; Shin, Han-Seung
Abstract: Background: Galangal is highly appreciated for its potential applications in food and medicine. In spite of its usage in food and herbal medicine in countries like Indonesia and Thailand, very limited data is accessible about its potential applications in therapeutics and pharmacology. It has been reported to be utilized in herbal medicines for treatment against diseases like hemorrhoids, abnormal menstruation, abdominal discomfort, and inflammation, among others. Scope and approach: The widespread use of galangal in food and traditional medicine has fascinated researchers all over the world looking for its enhanced medicinal capabilities, new bioactive compounds with nutraceutical potentials, and probable uses in medicine and pharmacology. A number of literature search methods like searching the related contents with the keywords such as Alpinia sp., galangal, antiviral, cardiovascular, neuroprotective, bioactive compounds, phytochemicals etc. in the web search engines' such as the Google search, Web of Science, Scopus, PubMed etc. were implemented. Key findings and conclusions: Conversely, there is no recent structured and ample review that summarizes the available data on these issues. In the current review, these topics are addressed in detail along with the investigation of scientific evidence supporting the vast applications of galangal in food and its medicinal properties, such as antiviral, cardiovascular and neuroprotective properties, together with the preclinical and clinical studies with galangal bioactive compounds. Highlights: Medicinal herbs are one of the imperative sources of drugs all over the world. A. galanga is highly appreciated for potential applications in food and medicine. Treatment in hemorrhoids, abnormal menstruation, abdominal distress, inflammation. Vast applications as antiviral, cardiovascular and neuroprotective properties. This review aspires to integrate information on customary attributes of galangal.